Monitoring and control of the multihead weighing process through a modified control chart (2017)
Modified control charts are used to monitor and control manufacturing processes which are considered to be six-sigma processes. The use of these charts is based on the idea that the cost of identifying and correcting special causes is much higher than the cost of off-target products. Therefore, the process mean is essentially acceptable as long as it is anywhere within the specification limits. These concepts are applied to the packaging process in multihead weighers. The weight of the packed product, seen as the quality characteristic to be monitored, must be as close to a specified target weight as possible and comply with applicable regulations. The packaging process was previously optimized and improved using a packaging strategy, which was evaluated through a proposed packing algorithm. In this way, a set of numerical experiments were conducted to examine the solutions generated, which were subsequently monitored.